2019
DOI: 10.4012/dmj.2018-008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of discoloration of sound/demineralized root dentin with silver diamine fluoride: <i>In-vitro</i> study

Abstract: The objective was to evaluate the effect of application of silver diamine fluoride (SDF) on discoloration of demineralized dentin over time. Dentin specimens were divided into four groups according to time of dentin demineralization. A 38% SDF solution was then applied to the dentin surfaces. Half of the specimens were placed in light-proof boxes while the remainder were exposed to light. Both groups were maintained at 37˚C. Color change was determined using a spectrophotometer at different time intervals. SEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 28 publications
1
32
0
2
Order By: Relevance
“…The investigators in a study concluded that the degree of dentin demineralization led to a significant increase in the rate of dentin color change after application of SDF. 19 However, a significant number of parents below the mean income accepted SDF discoloration in front teeth when compared to the parents with income above it. This can be due to the superficial or partial knowledge and lack of awareness among the parents about importance of primary teeth w.r.t.…”
Section: Discussionmentioning
confidence: 99%
“…The investigators in a study concluded that the degree of dentin demineralization led to a significant increase in the rate of dentin color change after application of SDF. 19 However, a significant number of parents below the mean income accepted SDF discoloration in front teeth when compared to the parents with income above it. This can be due to the superficial or partial knowledge and lack of awareness among the parents about importance of primary teeth w.r.t.…”
Section: Discussionmentioning
confidence: 99%
“…Both sound and demineralized dentin proved to have antibacterial properties after mechanical brushing in the SDF-treated dentin group. In the current study, the dentin was demineralized for 13 h in EDTA solution to simulate the severelydemineralized dentin condition 14 . The load (250 g), brushing time and frequency used in the tooth brushing test were considered to closely replicate the daily situation 16,17 as oral healthcare measures (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the silver reactions with the mineral phase, SDF application results in formation of silver phosphate 20 . However, silver phosphate is an unstable compound and reduces gradually into metallic silver by reducing agents such as light exposure 14 or replaced by silver chloride after immersion in artificial saliva 21 and the formation of metallic silver 6,22 . All the previously mentioned silver compounds contribute to hardening and protection of the dentin surface as well as the formation of the dark stains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations